2004
DOI: 10.1182/blood.v104.11.310.310
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of 18F-Fluorodeoxyglucose Positron Emission Tomography (FDG PET) Performed after Two Cycles of Standard Chemotherapy (CT) on Treatment Outcome in Hodgkin Disease.

Abstract: Objectives: Several prognostic models based on simple clinical variables have been proposed for Hodgkin’s Disease (HD); however, when applied in a prospective way, they showed unsatisfactory predictive value and scarce reproducibility. The prognostic role of early evaluation of treatment response by TC or Gallium scan has been proved in the past. We report here the preliminary results of a clinical trial on the prognostic role of FDG PET scan performed very early during treatment in advanced stage HD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 0 publications
6
60
0
4
Order By: Relevance
“…PET results in our patients are in line with other recent reports on 84% PFS of interim PET-negative patients [19]. However, these figures are lower than initial studies, who reported more than 90% PFS in interim PET-negative patients [10,11,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PET results in our patients are in line with other recent reports on 84% PFS of interim PET-negative patients [19]. However, these figures are lower than initial studies, who reported more than 90% PFS in interim PET-negative patients [10,11,19].…”
Section: Discussionsupporting
confidence: 92%
“…In 2006, Gallamini et al and Hutchings et al reported that PET examination with [ 18 F]fluorodeoxyglucose (FDG) after 2 cycles of standard chemotherapy, later on termed "interim-positron emission tomography (PET)", discriminates PET-negative patients with a very high probability of disease control with the standard chemotherapy regimen Adriamycin, Bleomycin, Vinblastine, Dacarbazine (ABVD), from PET-positive patients where standard therapy is most likely to fail [10,11]. These data were confirmed by several studies on patient groups with limited or advanced stage disease treated with ABVD, while the prognostic value of interim PET for patients treated with BEACOPP is not well established [12][13][14][15].…”
Section: Cd68+ Cell Count Early Evaluation With Pet and Plasma Tarc mentioning
confidence: 99%
“…The 5-year relapse rate was 3.4% in the routine surveillance group and 7.4% in the clinical surveillance group, which are similar to recent studies in which PET-adapted therapy was used and event-free survival was in the 90% to 96% range. [24][25][26][27][28] A recent study that examined patients with cHL who achieved remission with frontline therapy and were followed by routine surveillance imaging versus clinical surveillance had relapse and overall survival rates similar those in our patients. 29 Our study focused on patients who achieved complete remission (defined by PET scan) with frontline therapy.…”
Section: Discussionsupporting
confidence: 68%
“…The use of PET scans to predict response to chemotherapy in patients with advanced disease is being explored. Gallamini et al [17] prospectively studied 108 patients to determine whether a PET scan can predict treatment outcome in advanced-stage HD. All patients underwent a PET scan after two cycles of chemotherapy, and recurrences were confirmed by biopsy.…”
Section: Predicting Relapse and Improving Therapymentioning
confidence: 99%